2008
DOI: 10.1038/ijo.2008.177
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross-Sectional Study

Abstract: Objective: To provide an overview of the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross-Sectional Study (HELENA-CSS) design, with particular attention to its quality control procedures. Other important methodological aspects are described in detail throughout this supplement. Design: Description of the HELENA-CSS sampling and recruitment approaches, standardization and harmonization processes, data collection and analysis strategies and quality control activities. Results: The HELENA-CSS is a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
306
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(321 citation statements)
references
References 15 publications
3
306
0
5
Order By: Relevance
“…To begin with, the HELENA-CSS cohort is not a fully representative European sample, since due to the selection procedure of classes from all schools in the chosen cities representativeness can be at best achieved on the city level. However, this procedure was anticipated to give a fair approximation of the average situation, if the objective was to only describe the adolescents' characteristics, as was the case in the present study (27) . Furthermore, the 24 h recall used in the HELENA Study has been shown to be prone to under-reporting in a validation study (32,74) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To begin with, the HELENA-CSS cohort is not a fully representative European sample, since due to the selection procedure of classes from all schools in the chosen cities representativeness can be at best achieved on the city level. However, this procedure was anticipated to give a fair approximation of the average situation, if the objective was to only describe the adolescents' characteristics, as was the case in the present study (27) . Furthermore, the 24 h recall used in the HELENA Study has been shown to be prone to under-reporting in a validation study (32,74) .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about the study has been reported elsewhere (27,28) . The main objective of HELENA-CSS was to obtain reliable and comparable data on a variety of nutritional and health-related parameters in a representative sample of 3528 European adolescents (boys and girls aged 12?5-17?5 years) (28,29) .…”
Section: Study Design and Samplementioning
confidence: 99%
“…The HELENA-CSS study is a multi-centre, cross-sectional study performed in ten European cities that was designed to obtain reliable and comparable data on a broad battery of relevant nutrition and health-related parameters of a sample of European adolescents: 19,20 dietary intake, food choices and preferences, anthropometry, serum indicators of lipid metabolism and glucose metabolism, vitamin and mineral status, immunological markers, physical activity, fitness and genetic markers.…”
Section: Subjectsmentioning
confidence: 99%
“…19,20 A total of 392 adolescents were measured in Zaragoza (Spain), and 365 (182 female and 183 male participants) had valid DXA and PA data, and were then included in this study. After receiving complete information about the aims and methods of the study, all adolescents and their parents or guardians signed the informed written consent.…”
Section: Subjectsmentioning
confidence: 99%
“…From these forty-eight articles, sixteen articles were selected which best described the background to the project or the method used; one to three articles were typically selected per project, with the exception of the ToyBox study where articles obtained from authors were used in favour of the sourced article. Reviewing the reference lists yielded eighteen further articles in which the methods were described (29,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) .…”
Section: Public Health Nutritionmentioning
confidence: 99%